2011
DOI: 10.1007/s11886-010-0162-1
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Prevention in Atrial Fibrillation: Atrial Appendage Closure

Abstract: The left atrial appendage (LAA) is the primary nonvalvular cause of cardioembolic stroke in patients with atrial fibrillation (AF). Warfarin and direct thrombin inhibitors such as dabigatran are presumed to prevent formation of LAA thrombus, and are first-line treatments to prevent ischemic stroke in AF. However, these medications carry many contraindications such as hemorrhage, and can interact with many drugs and supplements. Epicardial and endovascular techniques for occlusion of LAA are being explored, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
8
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 48 publications
3
8
1
Order By: Relevance
“…Although the clinical significance of ISLL warrants further investigation, ISLL in patients with an elevated thromboembolic risk has likely the potential to harbor intracardiac thrombi and serve as a major threat for embolic events. Furthermore, it has been proposed that ISLL may actually be worse than no occlusion at all, given that reduced blood flow velocities in and out of ISLL may indeed promote a higher risk of thrombus formation . Consistent with this, patients 2 and 4 suffered embolic strokes shortly following surgical ligation of the LAA (within 3 weeks and 10 days, respectively).…”
Section: Discussionmentioning
confidence: 87%
“…Although the clinical significance of ISLL warrants further investigation, ISLL in patients with an elevated thromboembolic risk has likely the potential to harbor intracardiac thrombi and serve as a major threat for embolic events. Furthermore, it has been proposed that ISLL may actually be worse than no occlusion at all, given that reduced blood flow velocities in and out of ISLL may indeed promote a higher risk of thrombus formation . Consistent with this, patients 2 and 4 suffered embolic strokes shortly following surgical ligation of the LAA (within 3 weeks and 10 days, respectively).…”
Section: Discussionmentioning
confidence: 87%
“…Numerous studies have shown that the LAA is an important source of potential emboli. 9,17 Moreover, the latest iteration of the CMP (the CMP IV), as well as previous iterations of the CMP, have been shown to achieve drug-free freedom from AF of at least 84% of patients at 2 years postoperatively. 18 …”
Section: Discussionmentioning
confidence: 99%
“…68 The efficacy of the CMP for decreasing stroke risk has been attributed to both its success at restoring sinus rhythm and the amputation or exclusion of the left atrial appendage (LAA). 9 …”
mentioning
confidence: 99%
“…Stroke prevention is a primary goal in AF treatment, since 87% of strokes are believed to be thromboembolic, and patients with AF, whether permanent or paroxysmal, have a five-fold risk of stroke in comparison to a matched population in sinus rhythm 2 . This risk increases with age, from 1.5% / year in the 50-59-yearold age group to 23.5% in the 80-89-year-old age group 1,3 . Accordingly, oral anticoagulation for stroke prevention in AF patients has a class I, level of evidence A recommendation 4 .…”
Section: Introductionmentioning
confidence: 94%